Development of virtual classroom for interactive education on the web - Hamouda, Abdel Magid Salem; Tan, Jo Pei (2000)
Multimedia technology provides a valuable resource to enhance the teaching and learning experience. The ability to combine practical applications, visualization of complex mathematical subjects, virtual labs, and guided use of simulation software is among the advantages of technology-based education. In this paper we describe the main features of several multimedia tutorials for strength of material course. An interactive and dynamic homepage together with discussion board, self-grading quiz and virtual lab were developed.